2013
DOI: 10.1055/s-0032-1326268
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing fanning with standard technique for endoscopic ultrasound-guided fine-needle aspiration of solid pancreatic mass lesions

Abstract: Background and study aims The fanning technique for endoscopic ultrasound-guided fine-needle aspiration (EUS–FNA) involves sampling multiple areas within a lesion with each pass. The aim of this study was to compare the fanning and standard techniques for EUS–FNA of solid pancreatic masses. Patients and methods Consecutive patients with solid pancreatic mass lesions were randomized to undergo EUS–FNA using either the standard or the fanning technique. The main outcome measure was the median number of passes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
176
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(186 citation statements)
references
References 19 publications
0
176
0
6
Order By: Relevance
“…Therefore, methods for obtaining sufficient specimens for immunostaining are required. In two previous reports, Larghi et al [19] used 19G needles, and Hasegawa et al [20] adopted the fanning method reported by Bang et al [25] in 2013. Moreover, Eloubeidi et al [26] performed EUS-FNA without negative pressure and diagnosed 13 cases of PNET.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, methods for obtaining sufficient specimens for immunostaining are required. In two previous reports, Larghi et al [19] used 19G needles, and Hasegawa et al [20] adopted the fanning method reported by Bang et al [25] in 2013. Moreover, Eloubeidi et al [26] performed EUS-FNA without negative pressure and diagnosed 13 cases of PNET.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized trial comparing the fanning and standard techniques, the diagnostic accuracy was nonsignificantly different, although better in the fanning technique (76% vs 96%), with a lower number of passes to establish the diagnosis and better sensitivity after the first pass [66].…”
Section: Endoscopic Ultrasound Fine-needle Aspirationmentioning
confidence: 90%
“…At EUS, during individual FNA passes, after puncturing the pancreatic mass, the stylet was removed, and the needle was moved to-and-fro, 12 to 16 times, at different areas within the lesion using the fanning technique. 10 As described in a previous report, suction was not applied, and the stylet was not reintroduced into the needle after the first pass in any patient. 11 …”
Section: Procedural Techniquementioning
confidence: 99%